Manajemen kompetensi dosen berbasis Islam dalam mewujudkan perguruan tinggi bermutu - Saepudin, Saepudin; Setiawati, Yanti Hasbian; Kartika, Ika; Junaedi, Junaedi (Ta’dibuna: Jurnal Pendidikan Islam, 2020)
This paper purpose to analyze the effectiveness of the management of Islamic based lecturer competencies to create quality tertiary institutions through strengthening the integration of lecturer characters by strengthening academic dan spiritual characters. The method used in this study uses library research. Data analysis was carried out through the application of an interactive analysis model involving three interrelated components dan determining the final result, namely data reduction, data presentation, conclusion dan verification. The results of this study indicate that Islamic based lecturer competency management in realizing a quality Islamic religious tertiary institution can be done through strengthening academic character by establishing policies, programs dan activities related to the management of lecturer competencies by academic procedures, namely, recruitment, selection dan placement. While strengthening the spiritual character of lecturers is done through strengthening competencies, da’wah, moral competence dan akidah competence. Abstrak Tulisan ini bertujuan untuk menganalisis efektivitas manajemen kompetensi dosen berbasis Islam untuk mewujudkan perguruan tinggi bermutu melalui penguatan integrasi karakter dosen dengan penguatan karakter akademik dan karakter spiritual. Penelitian ini menggunakan metode penelitian pustaka. Hasil penelitian menemukan bahwa pengelolaan kecakapan dosen berbasis Islam dalam mewujudkan perguruan tinggi keagamaan Islam yang bermutu dapat dilakukan melalui penguatan karakter akademik dengan cara menetapkan kebijakan, program dan kegiatan yang terkait dengan pengelolaan kompetensi dosen dengan prosedur akademi, yaitu, rekrutmen, seleksi dan penempatan. Sedangkan penguatan karakter spiritual dosen dilakukan melalui penguatan kompetensi, dakwah, kompetensi akhlak dan kompetensi akidah.